Developing a novel peer support intervention to promote resilience after stroke. (4th March 2016) - Sadler, Euan; Sarre, Sophie; Tinker, Anthea; Bhalla, Ajay; McKevitt, Christopher
Abstract: Stroke can lead to physical, mental and social long‐term consequences, with the incidence of stroke increasing with age. However, there is a lack of evidence of how to improve long‐term outcomes for people with stroke. Resilience, the ability to 'bounce back', flourish or thrive in the face of adversity improves mental health and quality of life in older adults. However, the role of resilience in adjustment after stroke has been little investigated. The purpose of this study is to report on the development and preliminary evaluation of a novel intervention to promote resilience after stroke. We applied the first two phases of the revised UK Medical Research Council (UKMRC) framework for the development and evaluation of complex interventions: intervention development (phase 1) and feasibility testing (phase 2). Methods involved reviewing existing evidence and theory, interviews with 22 older stroke survivors and 5 carers, and focus groups and interviews with 38 professionals to investigate their understandings of resilience and its role in adjustment after stroke. We used stakeholder consultation to co‐design the intervention and returned to the literature to develop its theoretical foundations. We developed a 6‐week group‐based peer support intervention to promote resilience after stroke. Theoretical mechanisms of peer support targeted were social learning, meaning‐making, helping others and social comparison. Preliminary evaluation with 11 older stroke survivors in a local community setting found that it was feasible to deliver the intervention, and acceptable to stroke survivors, peer facilitators, and professionals in stroke care and research. This study demonstrates the application of the revised UKMRC framework to systematically develop an empirically and theoretically robust intervention to promote resilience after stroke. A future randomised feasibility study is needed to determine whether a full trial is feasible with a larger sample and wider age range of people with stroke.